An Experiment in Manufacturing Blanks and Striking Coins*. (8th February 2017) - Williams, Rick
Abstract: In the second half of the 6th century BC four South Italian Greek colonial cities – Sybaris, Croton, Metapontum and Caulonia – were minting silver-copper alloy coins, all in the incuse fabric, with the same weight standard of c. 8gm. These incuse coins were to remain in production at Croton and Metapontum for the next 100 years. Coins hoards indicate that these four cities began minting their coinage at the outset as very fine, artistic – even exquisite – objects of fine crafts-manship. Each coin was thin (1mm), broad (30mm) and of a consistently uniform weight and diameter, and each coin was struck between dies of exceptional quality. During subsequent decades the diameter of the coinage was progressively reduced. At Monash University in 1980 we conducted experiments in coin manufacturing to determine how the minters at Croton in the 6th century produced these thin, incuse coins from only a small amount (8gm) of silver alloy, how they maintained a consistent weight standard across a century of minting, and why they progressively reduced the size of their coins during this period. It is well-known that the manufacturing processes of objects made from metal alloys can be revealed by examining their crystal structures. In our experiments in manufacturing broad, thin 'Monash coins', we examined the crystal structures at various stages throughout the process. To do this we made coin blanks of various diameters, all made from 8gm of silver-copper alloy. These blanks were subjected to hardness tests and photographs were made of the alloy's crystal microstructures. 'Coins' were then minted by striking blanks between two manufactured replica dies, and their microstructures were compared with the microstructures of a genuine Croton incuse coin fragment. This is the first time these results have been published.